Trust Integrated Congestion Aware Energy Efficient Routing forWireless Multimedia Sensor Networks (TCEER) - Chakraborty, Arpita; Ganguly, Srinjoy; Naskar, Mrinal Kanti; Karmakar, Anupam (Journal of computing and information technology, 2015)
Congestion control and energy consumption in Wireless Multimedia Sensor Network is a new research subject which has been ushered in through the introduction of multimedia sensor nodes that are capable of transmitting large volume of high bit rate heterogeneous multimedia data. Most of the existing congestion control algorithms for Wireless Sensor Networks do not discuss the impact of security attacks by the malicious nodes in network congestion. Sensor nodes are prone to failure and malicious nodes aggravate congestion by sending fake messages. Hence, isolation of malicious nodes from data routing path reduces congestion significantly. Considering that, we have proposed a new Trust Integrated Congestion Aware Energy Efficient Routing algorithm, in which malicious nodes are identified using the concept of trust. The parameter Node Potential is computed, on the basis of the trust value, congestion status, residual energy and the distance of the node from the base station, using Fuzzy Logic Controller. The source node selects the node with the highest potential in its one hop radio range for data transmission which is light weight as well as energy efficient. Finally, merits of the proposed scheme are discussed by comparing them with existing protocols and the study exhibits 25% improvements in network performance.